Pengaruh suhu penyimpanan terhadap kualitas hasil panen komoditas Brassicaceae - Murtiwulandari Murtiwulandari; Deshinta Tri Murty Archery; Megawati Haloho; Rendha Kinasih; Lois Hintanara Shine Tanggara; Yetero Hendikus Hulu; Krisdania Agaperesa; Novani Wahyu Khristanti; Yuli Kristiyanto; Surya Seno Pamungkas; Yoga Aji Handoko; Gabriella Desnata Yoan Anarki (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Postharvest handling is recommended to maintain the quality of crop commodities. Brassicaceae is the most popular commodities. The postharvest handling of the Brassicaceae is important to maintain the quality and freshness up to the hand of consumers. This research was conducted to observe the effect of storage temperature on the quality of Brassicaceaeafter seven day of storage. The water content analysis was performed using the gravimetric method, weight loss was analyzed using the weight difference percentage method, respiration rate was analyzed using the CO2 absorption method and continued with titration, Vitamin C content was analyzed using the idiometric titration method, chlorophyll and carotenoids were analyzed using spectroscopy methods using DMSO reagent.Storage of Brassicaceaein the freezer can maintain freshness and good product quality based on low carotenoid content, respiration rate and tissue weight loss value.